2011
DOI: 10.1515/secm.2011.027
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of unidirectional CF/Al composites

Abstract: The unidirectional carbon fi ber (CF) reinforced aluminum (Al) composites have been fabricated by the low pressure infi ltration (LPI) of molten Al into porous CF preform. Prior to the fabrication of the unidirectional CF/Al composites, the unidirectional CF preform was prepared by sintering of CFs and copper (Cu) particles under the spark plasma sintering (SPS). The compression strength of CF preform was examined to determine the infi ltration pressure of molten Al into CF preform. The effects of the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…On one hand, TC value of the alumina coating is relatively low (nearly 36 W m −1 K −1 [23]), which may have a bad effect on the improvement of TC of the composites. On the other hand, alumina coating can act as the diffusion barrier to reduce the formation of Al 4 C 3 , which is harmful to TC of the composites [12]. Therefore, the result of this study shows that the beneficial effect dominates the effect of alumina coating on TC values of the composites.…”
Section: Effect Of Alumina Coatingmentioning
confidence: 70%
See 2 more Smart Citations
“…On one hand, TC value of the alumina coating is relatively low (nearly 36 W m −1 K −1 [23]), which may have a bad effect on the improvement of TC of the composites. On the other hand, alumina coating can act as the diffusion barrier to reduce the formation of Al 4 C 3 , which is harmful to TC of the composites [12]. Therefore, the result of this study shows that the beneficial effect dominates the effect of alumina coating on TC values of the composites.…”
Section: Effect Of Alumina Coatingmentioning
confidence: 70%
“…For SCF-Al composites, it is widely accepted that carbon fibres would react with aluminium to form brittle Al 4 C 3 , which is harmful to both mechanical and thermal properties of the composites [11][12][13][14]. An effective method to solve this problem is to coat the carbon fibres with protection coatings [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hihara [12] found that the aluminum carbide hydrolyzed at a rate of ∼ 1%/h indicated that the degradation resistance of G/Al composites would be severely compromised by the presence of Al 4 C 3 . The reason is that Al 4 C 3 has an unstable chemical property, absorbing water in the surrounding medium and reacting to produce CH 4 and Al(OH) 3 . More over, the expansion of these products in the interface leads to the peeling of reinforcements from the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Although the MMCs are very attractive materials for automobile industry, the raw materials and its manufacturing method are not cost effective compared with the conventional materials and its manufacturing system. However, the low-pressure infiltration method [5][6][7] is one of the useful casting methods for MMCs, due to apply low-pressure in comparison with high pressure casting such as die casting and squeeze casting. 8,9 Furthermore, low pressure is able to produce complex/ large shape and accomplish high cost-performance.…”
Section: Introductionmentioning
confidence: 99%